Duning in Rills on Unpaved Roads in Uganda (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
Dunes on non-paved roads develop as a result of general construction designs especially in the drainage. They are active features which block up drainage rills and parts of the roads causing road rutting, deep mudding and flooding. Shear stress, erosion, and deposition due to the discharge were the main factors in the equation formation and analysis. An equation is constructed to determine their formation and effects on gravel road dunes. It is finally tested with a numerical example using cross-sectional field and laboratory results data. Various experiments like sieve analysis, measuring road dune sizes with respect to slope size, rain intensity, and road widths were used in the formulation and evaluation of the equation for this study. Key findings of this paper include among others dune formation rates in road rills and possible timely control. The model equation constructed is expected to help in various road design and maintenance practices.